KAJIAN KARAKTERISTIK HARMONIK PASANG SURUT DENGAN METODE ADMIRALTY DI MALUKU UTARA - ANDINI, MAULYDIA ANDIS (Pusdiklat BMKG, 2022)
North Maluku is one of the youngest first-level administrative division of Indonesia with a total area of 140.366,32 km2. The territorial waters of this province are larger than the continents. By this condition, the ecosystem tends to have sea anomaly vulnerability that might cause sea level variation such as tides. This article provides an overview over components and tidal types in North Maluku waters. Quantitative analysis using Admiralty method is carried out in this study. There are about 6 points of research sites in this province were being analyzed. The result indicates that all of 6 points research sites demonstrating a similarity final result of Formzahl value that is between 0.25 and 1.5 with varied water level parameters. It means that North Maluku waters have mixed tide prevailing semidiurnal tidal type. Therefore, this article is expected to be useful for supporting the safety and regional development in North Maluku and also could be a reference for subsequent research.